Nanomaterials in drug delivery, imaging, and tissue engineering - Tiwari, Ashutosh; Tiwari, Atul (Wiley ; Scrivener Publishing, 2013)
"Nanoscopic therapeutic systems incorporate therapeutic agents, molecular targeting and diagnostic imaging capabilities and are emerging as the next generation of multifarious nanomedicine to improve the therapeutic outcome including chemo and translational therapy. This reference work is one of the first to cover Nanotheragnostics which is the new edge of nanomedicine combining both diagnostic and therapeutic elements at nano level.This large multidisciplinary reference work is has four main parts: Biocompatible Nanomaterials; Nanomedicine: Drug Gene and Cell Delivery; Multi-functional Nanocarrier: Diagnosis, Imaging and Treatment; Tissue Engineering/Regenerative Medicine"--Resumé vydavatele
Keywords: nanomedicína; diagnostické zobrazovací metody; tkáňové inženýrství; nanočástice; léky; navrhování léčiv; farmakokinetika; nanomedicine; diagnostic imaging methods; tissue engineering; nanoparticles; drugs; drug design; pharmacokinetics; kolektivní monografie; elektronické knihy; collective monographs; electronic books